Pengungkapan environmental, social, governance (ESG) dalam meningkatkan nilai perusahaan publik di Bursa Efek Indonesia - Fiki Kartika; Arief Dermawan; Faza Hudaya (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
Along with the development of the economy in Indonesia, the development of sustainability aspects in Indonesia has also received a good response. By carrying out Environmental, Social, and Governance (ESG) disclosures and regulations from regulatory agencies, public understanding of sustainability investment is hoped to continue to increase. Public awareness of ESG-based investments has continued to increase in recent years. ESG is a company standard in investment practices that integrates and implements its policies in line with environmental, social, and governance concepts. This study aimed to determine the effect of ESG on company value in companies listed on the Indonesia Stock Exchange (IDX), 2017-2021 period. The sample for this research is a company listed on the IDX for the 2017-2021 period. Sampling technique using purposive sampling. The data analysis used in this study is multiple linear regression. The analysis results conclude that Environmental, Social, and Governance (ESG) has not strongly influenced the value of companies listed on the IDX for the 2017-2021 period.